Market Reaction to Dividend Annoucements During Bear and Bull Periods - Nurul Hazemira, Abd Rahman (2010)
The stock market and economic activity move in similar cyclical patterns. This fundamental relationship has important ramifications. Firstly, it is solid evidence that stock prices are meaningful in the sense of reflecting real economic variables and not simply random numbers driven by the psyche, sunspots or the pronouncements of self-appointed seers. This study examines the short time price effect of dividend announcements during a bear market and a bull market. The data being used here is gathered from the years of 2000 - 2002, the years after the Asian financial crisis in 1998 and from the years of 2005 - 2007 when investors experienced large capital gains all around the world. The data consists of final dividend announcements and intact observations. The aim of this study is to find out differences in abnormal returns of dividend announcement differ during a bear and a bull market. Generally stated, the aim is to find out do investors value dividends more during a bear market than a bull market and can this be proved by using statistical test. This study is classified as a quantitative study and applies some form of statistical analysis. Therefore, linear regression analysis has been used. The empirical results from this study support that the abnormal returns of dividend announcements during the bear market were positively higher than those declared during a bull market. Thus, investors seem to value dividends more when stock prices are falling. Whereas abnormal returns of dividend announcement during a bull market are slightly smaller than a bear market may due to the investment opportunities by using internal funding that lead to cheaper cost of financing than external financing. The result overall samples state that the abnormal returns during the bear market were positively and slightly higher than during the bull market.